SITE INDEX MODEL FOR NATURAL STANDS OF REBOLLO OAK (Quercus pyrenaica Willd.) IN GALICIA, NW IBERIAN PENINSULA - Díaz-Maroto, Ignacio Javier (2010)
Data from stem analysis of 56 dominant trees of Quercus pyrenaica Willd., in natural stands in Galicia (NW Iberian Peninsula), were used to evaluate four dynamic site equations derived with the Generalized Algebraic Difference Approach (GADA). All the equations are base-age invariant and directly estimate height and site index from any height and age. The fittings were made using a data structure involving all possible growth intervals. The GADA formulation derived on the basis of the Bertalanffy-Richards model by considering the asymptote and the initial pattern parameters as related to site productivity. It is therefore recommended for height growth prediction and site classification for natural stands of rebollo oak in Galicia. The autocorrelation was analyzed with a test of residuals using Durbin’s t-test without reaching a manifest result of autocorrelation between managed data.